Omafuvwe Joseph Mudiare Performance of ISIAMOD and SWAP models in estimating Soil water balance components of a maize crop (Sammaz-28) under Rain-Fed condition - Ibrahim.Aliyu Salisu; Evonameh Igbadun,Henry (University of Eloued جامعة الوادي, 2024)
In this paper, the performance of Irrigation Scheduling Impact Assessment model (ISIAMOD) and Soil-Water-Atmosphere-Plant (SWAP) relationship model in estimating soil water balance of a cropped field under rainfall condition was studied under a sandy clayed loamy soil at the research field of the department of Agricultural Engineering, Ahmadu Bello University, Samaru, Zaria-Nigeria. Soil water balance data from the field study were used as reference values for the models performance evaluations. The statistical indicators used to compare the performance of the models were coefficient of residual mass (CRM), modelling efficiency (EF) and root mean square error (RMSE). The results showed that the two models satisfactorily simulated soil water balance components as their output compared closely to field measured data. CRM showed that ISIAMOD has the tendency of underestimating the ET, T, and Ecrop by a value which ranges from 2.5 to 6.0 % while SWAP has the tendency of overestimating the same components which ranges from 2.0 to 9 %. The modeling efficiencies of the two models range from 84 to 90 %, except for evaporation processes which ranges from 54 to 62 %. The RMSE of the two models ranges from 0.29 to 0.86. They both simulated the seasonal run-off and drainage well. The results show that the two models can be used for determination of soil water balance components of cropped soil and for analyzing a better water management option for agricultural production.
Article
Keywords: Simulation model; Soil Water Balance; Water management; ISIAMOD.